Potential biomarkers in Behçet’s disease: monocyte, neutrophil, platelet, and C-reactive protein to albumin ratios - Mestan Sahin; Cansu Celin Karakose; Meltem Alkan Melikoglu (Rheumatology)
Introduction The objective of this cross-sectional study was to evaluate the monocyte to albumin ratio (MAR), neutrophil to albumin ratio (NAR), platelet to albumin ratio (PAR), and C-reactive protein to albumin ratio (CAR) as potential biomarkers for disease activity in patients with Behçet’s disease (BD).